2008
DOI: 10.1021/bc700264g
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Dendrimers with Core Functionality for Biological Applications

Abstract: The synthesis of a variety of core functionalized PEGylated polyester dendrimers and their in vitro and in vivo properties are described in this report. These water-soluble dendrimers have been designed to carry eight functional groups on their dendritic core for a variety of biological applications such as drug delivery and in vivo imaging as well as eight solubilizing groups. Using a common symmetrical aliphatic ester dendritic core and trifunctional amino acid moieties, a library of dendrimers with phenols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 39 publications
6
130
0
4
Order By: Relevance
“…6B), with symmetry about the core, generated by divergent growth of a bis-2,2-hydroxymethylpropionic acid (bisHMPA) from a pentaerythritol core. 108 The bisHMPA block was then functionalized using a trifunctional amino acid, by EDC coupling to the carboxylic acid. PEGylation of the terminal amines through carbamate linkages leaves the third functional group available for modification at the dendritic core.…”
Section: Pegylated Dendrimer Therapeutic Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…6B), with symmetry about the core, generated by divergent growth of a bis-2,2-hydroxymethylpropionic acid (bisHMPA) from a pentaerythritol core. 108 The bisHMPA block was then functionalized using a trifunctional amino acid, by EDC coupling to the carboxylic acid. PEGylation of the terminal amines through carbamate linkages leaves the third functional group available for modification at the dendritic core.…”
Section: Pegylated Dendrimer Therapeutic Platformsmentioning
confidence: 99%
“…To examine the capacity of the dendrimers for conjugation with a small molecule drug, DOX was conjugated again by a hydrazone linkage. 108 Biodegradability and biodistribution studies demonstrated increased half-lives relative to unmodified DOX. This drug delivery system was found to be comparable to DOXIL, the current PEGylated version of DOX, in terms of amount of drug delivered to the tumor.…”
Section: Pegylated Dendrimer Therapeutic Platformsmentioning
confidence: 99%
“…There has been revitalized interest in the preparation of polymeric nanoparticles due to the use of these tailor-made materials in a variety of applications, such as microelectronics [1,2], drug-delivery systems [3][4][5][6][7] and polymer processing [8][9][10]. Recently, several strategies were employed for the preparation of polymeric nanoparticles, including intramolecular cross-linking of single polymer chains containing cross-linkable groups in ultra-diluted reaction conditions [11][12][13][14][15][16][17] and single-chain collapse of macromolecules containing suitable reactive groups along the chain with bifunctional cross-linkers [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Fréchet and coworkers have contributed tremendously to the area of polyester dendrimers [56,57,96,97,126,[142][143][144][145][146][147]. In early 2000, this group prepared and evaluated various dendritic architectures composed of a polyester dendritic scaffold based on the monomer unit bis-HMPA for their suitability as drug carriers both in vitro and in vivo [63].…”
Section: Advances In Polyester Dendrimers For Drug Delivery Applicationsmentioning
confidence: 99%